Domestic, Foreign Direct Investment and Economic Growth Nexus in Selected African Countries: Array - Gidigbi, Matthew Oladapo; Donga, Manu (Acta Universitatis Danubius. Œconomica, 2021)
This paper assesses the impacts of investment on economic growth in Africa. The study used secondary data and selected thirty African countries based on data availability and covering the period of thirty-four years starting from 1980. The study was found to be imperative because extant studies are of mixed results, with the view that the negative relationship between investment and economic growth is peculiar with developing countries. Panel Estimated Generalised Least Squares (EGLS) with pooled, fixed and random effects estimations were carried out, but the results of the Pooled Panel EGLS with cross-section Seemingly Unrelated Regression (SUR) weight estimation were explained. The paper found out that domestic investment contributes 19.36 per cent to economic outputs in response to a percentage increment, while foreign direct investment (FDI) and current account balances contribute 13.21 and 3.61 per cent respectively to economic outputs when increased by a percentage. This paper concluded that the investment is very relevant to the economic growth in the continent, though its impact is only greater than that of FDI by approximately 6 percentage points, which is still very small. The paper recommends investment promotion strategies to enhance more local participation in investment processes and opportunities. Also, the principle of political stability and peaceful transition should be encouraged; and structural constraints should be effectively managed to enhance absorptive capacity and more foreign direct investment in the continent. Keywords: Investment, Foreign direct investment, Economic growth, Current Account, Panel data, Regional economics Jel Code: O16, F21, F43, F32, C33, R11